2021
DOI: 10.2147/rmhp.s314510
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Pesticide-Metabolizing Enzymes and Transporters in Agricultural Workers and Thyroid Hormone Levels

Abstract: Purpose Chronic exposure to pesticides has been associated with thyroid dysfunction owing to their endocrine disruption ability. Genetic variations in genes encoding phase I and II enzymes and phase III transporters are partly responsible for individual responses to chemical pesticides. This study investigated the association between variations in genes involved in pesticide metabolism and altered thyroid hormone concentrations. Methods We assessed thyroid-stimulating h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The geometric mean of FT 4 serum levels among groups exposed to only insecticide application was slightly higher compared to the unexposed (36,38). These results were similar to that of the groups exposed to various pesticide types (39,43,47,51) as demonstrated in Table 1.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The geometric mean of FT 4 serum levels among groups exposed to only insecticide application was slightly higher compared to the unexposed (36,38). These results were similar to that of the groups exposed to various pesticide types (39,43,47,51) as demonstrated in Table 1.…”
Section: Discussionsupporting
confidence: 83%
“…Ten of eleven studies conducted with either farmers or farmworkers showed that exposure to various types of pesticides application significantly affected the level of thyroid hormone compared to unexposed groups (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). However, the remaining one indicated that the difference in thyroid hormone levels among both exposed and unexposed groups was statistically insignificant (37) as presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations